The winter place - Yates, Alexander (2015)
Upon their father's death, Tess and her younger brother, Axel, leave New York for their grandparents' home in Finland, where they learn that a bear they both saw is the spirit of their mother, the strange man with her is the keeper of souls, and he wants Axel, already plagued with the disease that killed their mother, to replace him.
Keywords: Supernatural -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Death -- Fiction; Soul -- Fiction; Grandparents -- Fiction; Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Death -- Juvenile fiction; Soul -- Juvenile fiction; Grandparents -- Juvenile fiction; Finland -- Fiction; Finland -- Juvenile fiction; Paranormal fiction; Young adult fiction